Identifikasi Model Bisnis Di PT Berkat Abadi Korindo Kota Bitung - Ompi, Chrysostomus Yudhistira; Katiandagho, Theodora M.; Lumingkewas, Jelly R.D. (AGRI-SOSIOEKONOMI, 2023)
This study aims to identify the business model implemented by PT Berkat Abadi Korindo and map the business model implemented. This research was conducted from September to October 2022. The location was chosen deliberately. The types of data used in this research are primary data and secondary data. Primary data were obtained through in-depth interviews and FGDs with owners, financial and production managers from PT. Korindo's Eternal Blessing. Meanwhile, secondary data was obtained through the Industry and Trade Office of Bitung City, literature, journals and research reports. The results of the study show that the customer segment of PT Berkat Abadi Korindo is a company selling fishing nets. Then the proposition offered is the customization of coir rope with quality standards in accordance with SNI. PT Berkat Abadi uses a link as a channel to reach its customers. Then the relationship with customers is carried out in a personal way. The revenus stream element from PT Berkat Abadi Korindo only sells coconut fiber rope. Furthermore, the main resources used are production machines with key activities in the form of production activities. While the main partnerships that support the running of the company are Liaison and Suppliers in the last element in the form of a cost structure containing fixed costs and variable costs. After obtaining information from the business model environment, it was identified that the business model used by PT Berkat Abadi Korindo was the Business Model Canvas.